Implementation of Islamic Business Ethics Principles in MSMEs in Kutai Kartanegara: A Study at SRC Kurnia Store Tenggarong Seberang - Muhammad Muliadi; Rais Abdullah (FEB Universitas Mulawarman, 2025)
This research aims to determine the implementation of Islamic business ethics principles in Micro, Small and Medium Enterprises (MSMEs) at SRC Kurnia Store Tenggarong Seberang. This research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. Research informants consist of store owners, employees, and customers of SRC Kurnia Store. Data analysis was carried out through data condensation, data presentation, triangulation, and drawing conclusions. The research results show that SRC Kurnia Store has implemented five principles of Islamic business ethics, namely: (1) Tawhid, although worship facilities are still limited; (2) Balance, with a fair salary system based on regional minimum wage and incentive provision; (3) Free Will, by implementing healthy competition without harming other traders; (4) Responsibility, by maintaining product quality and being responsive to customer complaints; and (5) Truth, by instilling a culture of honesty although price transparency is not yet optimal. This research concludes that SRC Kurnia Store has generally implemented the principles of Islamic business ethics well, but there are still aspects that need improvement such as providing adequate worship facilities and displaying price labels on all products